2019
DOI: 10.1038/s41598-019-51511-3
|View full text |Cite
|
Sign up to set email alerts
|

Thiotrophic bacterial symbiont induces polyphenism in giant ciliate host Zoothamnium niveum

Abstract: Evolutionary theory predicts potential shifts between cooperative and uncooperative behaviour under fluctuating environmental conditions. This leads to unstable benefits to the partners and restricts the evolution of dependence. High dependence is usually found in those hosts in which vertically transmitted symbionts provide nutrients reliably. Here we study host dependence in the marine, giant colonial ciliate Zoothamnium niveum and its vertically transmitted, nutritional, thiotrophic symbiont from an unstabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 87 publications
2
16
0
Order By: Relevance
“…two differently named organisms" 4 , and of its associated microbial consortium (= microbiome), could be indeed considered an important descriptor of the state of an organism, potentially influencing its development, physiology, and morphology. This opinion is in agreement with the findings of several previous studies [5][6][7][8][9][10][11][12][13][14] .…”
supporting
confidence: 93%
See 1 more Smart Citation
“…two differently named organisms" 4 , and of its associated microbial consortium (= microbiome), could be indeed considered an important descriptor of the state of an organism, potentially influencing its development, physiology, and morphology. This opinion is in agreement with the findings of several previous studies [5][6][7][8][9][10][11][12][13][14] .…”
supporting
confidence: 93%
“…the presence of stably associated organisms, whenever present. Indeed, the presence of these organisms can influence the host, its physiology, and its adaptability to the environment 6,12,13 ; moreover, in some cases it has been shown to influence also its morphology 5,14 , the fundamental parameter of traditional taxonomy.…”
Section: : E Alatus E Antarcticus E Balteatus E Charon E Crementioning
confidence: 99%
“…With a swarmer LT 50 of 39 h and a swim speed of 5 mm s -1 [42] dispersal over about 700 m can be accomplished given the swarmer swims in a straight line. Because the vertically transmitted symbiont on the swarmer [11,12], however, is lost under oxic conditions within 24 h [25], the maximal estimated swarmer dispersal distance can only be reached together with the symbiont if the swarmer migrates in the sulfidic boundary layer close to sulfide emitting surfaces. In oxic seawater, symbiotic swarmers only reach about 400 m distance and from there on the host travels aposymbiotically until it settles or dies.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in custom-designed flow-through chambers creating a steady flow of oxic seawater mixed with sulfide showed that growth was highest at sulfide concentrations between 3 and 33 μmol L -1 [21]. Yet, Zoothamnium was able to grow also aposymbiotically into smaller colonies under oxic conditions without sulfide [21,25]. We do not know, however, how long large symbiotically grown colonies can survive under oxic conditions when sulfide ceases and what happens to their symbionts.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in the lab showed that all swarmers lost their symbionts in two days and thus became aposymbiotic. Regardless of presence or absence of symbionts, the vast majority only settled in the presence of sulfide [31]. Once they have settled, they can grow aposymbiotically into small colonies with or without sulfide in custom-designed flow-through chambers with a steady flow of oxic seawater.…”
Section: Introductionmentioning
confidence: 99%